Pembangunan model kurikulum latihan SkiVes bagi program pengajian kejuruteraan pembelajaran berasaskan kerja / Mohd Ridhuan Mohd Jamil - Mohd Ridhuan , Mohd Jamil (2016)
This study aimed to develop a SkiVes training curriculum model for the engineering education program based on Work-Based Learning (WBL) in Malaysian Polytechnic. The construction of the model was intended to assist and guide the lecturers in carrying out the teaching and application of generic skills and values for the engineering students that enrolled in WBL education programme. This study used the method of Design and Developmental Research Approach introduced by Ritchey and Klien (2007) to develop the model. Based on this method, the study was divided into three phases. In the first phase, a survey using needs analysis was conducted on 65 students who had just finished studying engineering at the Malaysian Polytechnic based on WBL to see the need to train and deploy the elements of generic skills and values on themselves. The data was analyzed by descriptive statistics using the software Statistical Package for the Social Science (SPSS) version 21.0. The interpretation of this requirement was based on the mean value and standard deviation. In the second phase, Fuzzy Delphi Method (FDM) approach and Interpretive Structural Modeling (ISM) were exploited to develop a model based on the opinions and decisions of 12 and 9 panel of experts for Fuzzy Delphi Method (FDM) and Interpretive Structural Modeling (ISM) repectively. The data of Fuzzy Delphi Method (FDM) approach was interpreted based on the acceptance of its major components and elements accepted by a panel of experts. Meanwhile the Interpretive Structural Modeling (ISM) approach was the experts’ agreement on the position of each of the main components from the aspect of driving power and dependence power. The third phase was the usability evaluation model involving 21 experts of engineering lecturers evaluating the model using Modified Nominal Group Technique (Modified NGT). Engineering lecturers were selected because they were the target group that used the SkiVes training curriculum model, they were directly involved in the engineering study programme based on Work-based Learning (WBL) at the Malaysian Polytechnic. Acceptance percentage point score was calculated to determine the suitability of all components and elements in the model. Acceptance percentage point score must be above 70% for each component and element to be considered suitable and applicable. The overall findings of the first phase showed that the students stated that there were no educational training either on a scheduled basis or through the application in the field of courses followed, and there were no materials or resources directly focused on the elements of generic skills and values. Next the students agreed to be trained and to apply the elements of generic skills and values before they enrolled in the industry. Therefore, the study to construct SkiVes training curriculum model is required. Findings from the second phase generated the training curriculum model that involved 5 keys component and elements contained therein. The main components included the objectives, content, teaching aids, teaching strategies (delivery) and evaluation. Further, the findings showed that all three phases of the main components and elements were located at a suitable level and can be implemented since the score percentage value of above 70% was accomplished. This development of model is able to guide the engineering lecturers in the process of implementation and training involving generic skills and values for engineering programmes based on Work-Based Learning (WBL) that is implemented at the Malaysian Polytechnic.